The Bali Fintech Agenda. (Policy Papers; Policy Paper ;, 2018)
Rapid advances in financial technology are transforming the economic and financial landscape, offering wide-ranging opportunities while raising potential risks. Fintech can support potential growth and poverty reduction by strengthening financial development, inclusion, and efficiency-but it may pose risks to consumers and investors and, more broadly, to financial stability and integrity. National authorities are keen to foster fintech's potential benefits and to mitigate its possible risks. Many international and regional groupings are now examining various aspects of fintech, in line with their respective mandates. There have been calls for greater international cooperation and guidance about how to address emerging issues, with some also cautioning against premature policy responses. In response to these calls from member countries, the IMF and the World Bank staff have developed the Bali Fintech Agenda, summarized in Annex I of this paper. The Agenda brings together and advances key issues for policymakers and the international community to consider as individual countries formulate their policy approaches. It distills these considerations into 12 elements arising from the experiences of member countries. The Agenda offers a framework for the consideration of high-level issues by individual member countries, including in their own domestic policy discussions. It does not represent the work program of the IMF or the World Bank, nor does it aim to provide specific guidance or policy advice. The Agenda will help guide the focus of IMF and World Bank staff in their work on fintech issues within their expertise and mandate, inform their dialogue with national authorities, and help shape their contributions to the work of the standard-setting bodies and other relevant international institutions on fintech issues. Implications for the work programs of the IMF and World Bank will be developed and presented to their respective Executive Boards for guidance as the nature and scope of the membership's needs--in response to the Bali Fintech Agenda-become clearer.